ANALISIS KADAR UREUM, CREATININ, DAN ASAM URAT PADA OAT TB-PARU - Wibowo Wibowo; Yuliansyah Sundara Mulia; Sunarno Sunarno; Amir Su’udi; Rudi Hendro Putranto; Kurnia Kusumawati; Gita Iftitah Renitia (Poltekkes Kemenkes Bandung, 2023)
Tuberculosis (TB) is an infectious disease which is still a global health problem. At present, tuberculosis treatment is given in the form of a package in the form of fixed-dose combination anti-tuberculosis drugs in general, namely Rifampicin, Isoniazid, Ethambutol, and Pyranizamid. Anti-Tuberculosis is a long-term treatment. One of the side effects of using it can be nephrotoxic or destructive to cells in the kidney, which can decrease the kidney's excretory function with a marked increase in substances from blood chemistry, namely urea, creatinine, and uric acid. This study aimed to analyze urea, creatinine, and uric acid levels in patients with pulmonary tuberculosis consume Anti-Tuberculosis therapy at Dr. Lung Hospital. M. Goenawan Partowidigdo Cisarua Bogor. The research method was descriptive by taking secondary data from Gita Iftitah Renitia's research results. The descriptive tests analyzed DR-TB OAT side effects confirmed by laboratory results. The research result from the sample count, there were 243 patients, confirmed laboratory results found normal urea levels (20-40 mg/dL) in 97 people (59.5%); normal limit creatinine (0.5-1.5 mg/dL) 150 people (92%); uric acid was above normal (> 6 mg/dL) in 113 people (61.4%). The concluded that side effects of DR-TB OAT in the highest number of cases of uric acid levels above normal (> 6 mg/dL) were found in housewives.